Is measuring results in social services possible? The lived experiences of professionals in key positions. Issue 1 (2nd January 2022) - Eriksson, Therese; Janlöv, Ann-Christin
ABSTRACT: This study illuminates professionals in key positions and their lived experience of measuring results in social services. Human service organizations were chosen as a focus area since the social services are complex, and research is currently limited regarding this phenomenon. Eight professionals in key positions agreed to participate in the study and were interviewed individually. A phenomenological hermeneutical method inspired by the interpretation theory developed by Ricoeur was used to analyse their narrations. Firstly, by a naive reading, the phenomenon was sensed. Secondly, the structural analysis revealed three themes: having inner mixed feelings regarding performance measurement in social work, feeling questioned regarding professional competence, and feelings of being in an organization far removed from the core of social work. Thirdly, an interpreted comprehensive understanding was: Measuring results in social services is like putting a jigsaw puzzle together, where each piece has its special place. This puzzle still lacks pieces, and it is only when the complexity of measuring results in social work is understood that the puzzle can be put together in its entirety. The study indicates it is important to address uncertainties and mixed feelings among professionals in key positions in social work organizations to maintain work environments which promote professionals' health in relation to measuring for results.